2021
DOI: 10.2147/jpr.s311311
|View full text |Cite
|
Sign up to set email alerts
|

Global Research Trends of Herbal Medicine for Pain in Three Decades (1990–2019): A Bibliometric Analysis

Abstract: Purpose The aim of this study was to explore the global research trends of herbal medicine for pain from 1990 to 2019, using bibliometric methods, and explore international collaborations, intellectual structure, the evolution of active topics, emerging trends, and research frontiers. Methods Articles on herbal medicine for pain were retrieved from WoSCC. Two information visualization softwares including CiteSpace and HistCite were used to process bibliographic catalogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Korea (140 articles, 30.13%) and China (81 articles, 17.5%) are the countries that published the most papers in this field, and many universities and research institutes in these countries are also ranked high when analyzed by research organizations. It appears that East Asia is the leading continent of worldwide research on herbal medicine for obesity, and their results are similar to the results of other bibliometric analysis papers on herbal medicines [22,23] . In particular, research organizations in Korea published almost a quarter of the total number of articles in this study, and this may be due to the fact that various collaborative studies have been conducted at university research institutes where the Department of Oriental Medicine and Food Engineering were jointly established.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Korea (140 articles, 30.13%) and China (81 articles, 17.5%) are the countries that published the most papers in this field, and many universities and research institutes in these countries are also ranked high when analyzed by research organizations. It appears that East Asia is the leading continent of worldwide research on herbal medicine for obesity, and their results are similar to the results of other bibliometric analysis papers on herbal medicines [22,23] . In particular, research organizations in Korea published almost a quarter of the total number of articles in this study, and this may be due to the fact that various collaborative studies have been conducted at university research institutes where the Department of Oriental Medicine and Food Engineering were jointly established.…”
Section: Discussionsupporting
confidence: 82%
“…It appears that East Asia is the leading continent of worldwide research on herbal medicine for obesity, and their results are similar to the results of other bibliometric analysis papers on herbal medicines. [ 22 , 23 ] In particular, research organizations in Korea published almost a quarter of the total number of articles in this study, and this may be due to the fact that various collaborative studies have been conducted at university research institutes where the Department of Oriental Medicine and Food Engineering were jointly established. The subjects of research from these institutions were diverse, and the main subjects were clinical trial studies conducted to determine the efficacy and side effects of herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2014;Lin PH. et al, 2016;Arai et al, 2020;Wang and Meng, 2021). Recently, a number of clinical and experimental studies on various problems caused by cancer have been reported based on the scientific methodological approach for East Asian herbal medicine (EAHM) (Lin et al, 2019;Tsai et al, 2019;Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Scientometrics can well reveal the disciplinary development process, research status, and development trend and has been widely used in the research of various disciplines. Wang [ 4 ] explored the research trends of Chinese herbal medicine in relieving pain by applying scientometrics. Zhong [ 5 ] applied scientometrics to study the pathogenesis of epilepsy.…”
Section: Introductionmentioning
confidence: 99%